Performance Responsibility of the Information and Documentation Management Officer (PPID) of Padang City in Enhancing Public Information Disclosure - Shafira Risni; Rahmadhona Fitri Helmi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The performance responsibility of the Information and Documentation Management Officer (Pejabat Pengelola Informasi dan Dokumentasi [PPID]) is central to advancing public information transparency at the local government level; however, studies specifically addressing PPID performance responsibility remain limited. This study aimed to analyze the performance responsibility of the PPID of Padang City and to identify the challenges encountered in enhancing public information disclosure. A qualitative descriptive approach was employed, with data collected through interviews and documentation, while informants were selected using purposive sampling. Data were analyzed through the stages of data reduction, data display, and conclusion drawing based on the responsibility theory of Jabra and Dwivedi. The findings show that the PPID of Padang City has demonstrated a fairly good level of performance responsibility, as reflected in the implementation of one-stop services, the conduct of internal and external evaluations, and the provision of information that is accurate, fair, and timely. Nevertheless, several challenges persist, including limited human resources, suboptimal coordination among regional apparatus organizations, and the absence of an integrated public information system. The study concludes that strengthening inter-organizational coordination, enhancing human resource capacity, and optimizing digital information management are necessary to improve public information disclosure and support transparent, accountable, and participatory governance. These findings contribute to the understanding of performance responsibility in public information management at the local government level and offer practical directions for institutional improvement.